2000
DOI: 10.1103/physrevb.62.13915
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of ZrN superconducting films

Abstract: Superconductivity in nitrides presents intriguing aspects related to the role of optical phonons. In the present paper we report on high-quality superconducting zirconium nitride film preparation and characterization ͑including Raman scattering͒ as well as on both dc and microwave frequency transport properties. The hightemperature dc resistivity shows no evidence of saturation effects, possibly due to the low electron-phonon coupling. Surface impedance data can be well fitted by the standard BCS expressions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…This is in good agreement with the reported Raman studies for ZrN films reported by Constable et al [24]. The -1 ), of the bands is due to the superposed contributions of disorder of optical phonons and second order combination of acoustic and optical processes [25]. Nanoindentation provides a method of near surface measurements to reduce substrate effect because the direct observation of the contact impression size is not necessary.…”
Section: Methodssupporting
confidence: 78%
“…This is in good agreement with the reported Raman studies for ZrN films reported by Constable et al [24]. The -1 ), of the bands is due to the superposed contributions of disorder of optical phonons and second order combination of acoustic and optical processes [25]. Nanoindentation provides a method of near surface measurements to reduce substrate effect because the direct observation of the contact impression size is not necessary.…”
Section: Methodssupporting
confidence: 78%
“…Figure 4(a) shows the Raman spectra of an yttria stabilized t‐ZrO 2 sample well away from the nitrided surface and correspond to well‐known Raman spectra of the t‐ZrO 2 , as reported by several authors 1. Whereas a typical Raman spectrum from ZrN exhibits two pronounced bands [Figure 4(b)], which are related to the acoustic part and the optical part of the phonon spectrum, respectively 13,14. ZrN has an NaCl type cubic structure in which N atoms occupy all the four octahedral sites of the f.c.c.…”
Section: Resultssupporting
confidence: 69%
“…It has been proposed that the temperature-dependent resistivity of VN exhibits saturation [67,69], a sublinear decrease in resistivity with decreasing temperature, as is typical of A15-structure compounds [70][71][72] for which strong electron/phonon scattering reduces electron mean free paths to lengths comparable to interatomic spacings [73]. However, for VN, the temperature below which the slope dρ/dT decreases more rapidly coincides with the cubic-to-tetragonal phase-transition temperature (T c = 250 K) determined by temperature-dependent SAED (Fig.…”
Section: Vn Temperature-dependent Resistivitymentioning
confidence: 99%